1972
DOI: 10.1037/h0032394
|View full text |Cite
|
Sign up to set email alerts
|

Physical attractiveness and marital choice.

Abstract: The stimulus-value-role theory of marital choice holds that individuals tend to choose marital partners of comparable physical attractiveness to themselves. Physical attractiveness was measured by self-perception, perception of the partner, and appearance judged from photos. Actual couples were hypothesized to be significantly less discrepant on these variables than a control group contrived by randomly pairing the scores of men and women. The two samples consisted of 99 and 98 college couples, respectively, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
2
7

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(109 citation statements)
references
References 11 publications
6
94
2
7
Order By: Relevance
“…Indeed, when participants were free to choose their dating partner (as opposed to Walster et al's (1966) study where participants did not get to choose) they tended to choose partners that were similar to their physical attractiveness levels (Berscheid et al, 1971). Murstein (1972) found results to support the notion that individuals of "equitable marketvalue" are more likely to come together than individuals of "disparate market-value" (p.11).…”
Section: Theoretical and Empirical Precedentssupporting
confidence: 79%
“…Indeed, when participants were free to choose their dating partner (as opposed to Walster et al's (1966) study where participants did not get to choose) they tended to choose partners that were similar to their physical attractiveness levels (Berscheid et al, 1971). Murstein (1972) found results to support the notion that individuals of "equitable marketvalue" are more likely to come together than individuals of "disparate market-value" (p.11).…”
Section: Theoretical and Empirical Precedentssupporting
confidence: 79%
“…However, this applies only to the analysis in which they compared participants with different levels of self-rated attractiveness and not with independently judged attractiveness. There is inconsistent evidence concerning the strength of the relations between self-rated attractiveness with other-rated attractiveness (Weeden & Sabini, 2007; see also Murstein, 1972). As self-ratings in general are subject to numerous other influences (e.g., social comparison, self-esteem), we confine ourselves to other-rated attractiveness.…”
Section: Notesmentioning
confidence: 99%
“…Whereas assortative mating describes systematic patterns of nonrandom mating, the adjective positive narrows it down to nonrandom mating between individuals who are similar on one or more aspects. Indications for positive assortative mating among humans have been found repeatedly in correlational research in which similarity between partners concerned factors such as religion, attitudes, and personality characteristics (Botwin, Buss, & Shackelford, 1997;Feng & Baker, 1994;Little, Burt, & Perrett, 2006;Vandenberg, 1972), and, important in the present context, physical attractiveness (Chambers, Christiansen, & Kunz, 1983;Murstein, 1972;Price & Vandenberg, 1979; for a meta-analysis, see Feingold, 1988). Positive assortative mating seems to be functional in that higher degrees of similarity are associated with higher levels of relational and marital success (Cavior & Boblett, 1972;Keller, Thiessen, & Young, 1996;Little et al, 2006;Vandenberg, 1972;White, 1980) and with greater genetic relatedness, thus facilitating inclusive fitness (Thiessen & Gregg, 1980).…”
Section: Attractiveness Similaritymentioning
confidence: 99%
“…They concluded that the only important determinant of an individual's liking for his date was the date's physical attractiveness. Finally, Murstein (1972), investigating the idea that people select marital partners of similar physical attractiveness to themselves, concluded that physical attractiveness (both subjectively experienced and objectively measured) operates by what he calls exchange-market rules. That is, individuals with equal market value for physical attractiveness are more likely to associate in an intimate relationship than are individuals with disparate values.…”
mentioning
confidence: 99%